Imaginário social e educação: nos labirintos da formação inicial de professores - Silva, Monique da (2017)
This doctoral thesis in Education was developed in the Line of Research 1 – Formation, Knowledge and Professional Development of the Graduation Program in Education at Universidade Federal de Santa Maria (UFSM). The starting point for it was the formative background of the author in the Study and Research Group on Education and Social Imaginary GEPEIS and an academic curiosity on which are the imaginaries about education, school, being a teacher, being a student, and also the teaching praxis that the undergraduate students at final semesters in education courses at UFSM took. There is also a search on how the initial formation courses contribute to the change/maintaining of this imaginaries and the existent school structure. The general aim of the research was to dialogue with the imaginaries of final semesters scholars at UFSM education undergraduate courses about education in a constitutive perspective, in order to understand the way this initial formation courses contribute to the change/maintaining of this imaginaries and the existent school structure. The research theoretic basis is the Social Imaginary of Cornélius Castoriadis (1982). In this study, the concepts of radical imaginary, creation, imaginary significations, magma, symbolic, social imaginary, identity-conjunctive logic, imaginary institutions, instituted social imaginary, society, subjectivity, heteronomy and autonomy. The methodology was created by the author specially to this research, and it is called Kaleidoscope Method. The method was inspired on Edgar Morin's (2013) work and in the optical device kaleidoscope. It consists in working with several data building tools which combine and recombine among themselves through the investigation, looking for possible ways to achieve the research objectives. A socio-imaginary questionnaire and, a Document Analysis of each of the UFSM's twenty two education courses took place. Also, there were Cross Talks, conversation groups with final semester classes about the topics of research. Data were analyzed through Martin Heidegger (2011) and Hans-Georg Gadamer's (1997) Hermeneutics Analysis. The results correspond to three analysis pivots, classified into: who are the scholars in the education courses, where they arrive when first start at UFSM and which are the significations present in their imaginaries at the final formation stages. The scholars, in general, are from medium-low social backgrounds, and they see in the education courses their only chance to enter Higher Education. This courses have outdated curricula, bibliographies and organization; and the imaginary of teachers to be are based on the memory from the times they were students and on the ideal of school proposed by educational theories, what is a result of the lack of contact with the school during the initial formation. Nevertheless, with this investigative scenario, we understand that education courses are frail, and they need a reform of thinking, structure and objectives, as well as the schools. This happens because education needs to start to contribute to the subjects self-formation and to be connected to the society's symbolic universe and its political, ethical and social complexity.